HUBUNGAN ANTARA KONTROL DIRI DENGAN PERILAKU MEMBOLOS SISWA KELAS 7 SMP PGRI 6 BOGOR - Nurfadhilla Priandini, Dhea; Nawawi, Kholil; Isna Alfaien, Noor (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
Students who habitually skip class can be caused by a lack of self-control. Self-control is said to be the ability to control behavior, feelings, emotions, decisions and actions that arise out of will so that it can lead to a positive direction. This research aims to determine the relationship between self-control and truant behavior in grade 7 students at SMP PGRI 6 Bogor. The hypothesis proposed in this research is that there is a negative relationship between self-control and truant behavior. The subjects in this research were 97 students of SMP PGRI 6 Bogor. The sampling technique used is non-probability sampling technique. (Saturated Sampling). Research data was collected using two scales, namely the self-control scale and the truant behavior scale. Data collection techniques use primary data and secondary data. The results of the study showed that there was a negative relationship between self-control and truant behavior as indicated by a significance result of -0.199. This shows that there is a very significant negative relationship between self-control and truancy behavior of grade 7 students at SMP PGRI 6 Bogor